2017
DOI: 10.1097/mnm.0000000000000698
|View full text |Cite
|
Sign up to set email alerts
|

A 99mTc-labelled scFv antibody fragment that binds to prostate-specific membrane antigen

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Lastly, given its recombinant nature and inherent versatility [ 64 ], 4LB5 can be conjugated to other molecules or protein domains to boost its clinical efficacy (e.g., adding immunoreactive Fc domain or active RNAse enzyme [ 65 ]). In fact, scFv antibodies are currently being investigated in PCa to target cell surface molecules such as PSMA for diagnostic purposes [ 66 , 67 ]. The ability to bind a surface protein highly expressed in PCa makes 4LB5 a powerful potential theranostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, given its recombinant nature and inherent versatility [ 64 ], 4LB5 can be conjugated to other molecules or protein domains to boost its clinical efficacy (e.g., adding immunoreactive Fc domain or active RNAse enzyme [ 65 ]). In fact, scFv antibodies are currently being investigated in PCa to target cell surface molecules such as PSMA for diagnostic purposes [ 66 , 67 ]. The ability to bind a surface protein highly expressed in PCa makes 4LB5 a powerful potential theranostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…The PSMA-targeted scFv constructs were also developed from the huJ591 antibody (DOTA-cysteine-modified scFv fragment labeled with 64 Cu and its conjugate to DSPE-PEG micelles) for PET imaging [89]. Another studies reported that the scFvhuJ549 fragments labeled with 68 Ga ( 68 Ga-THPscFv), 99m Tc ( 99m Tc-scFv) and 89 Zr ( 89 Zr-scFv) showed also selective binding to the PSMA-expressing cells in vitro [84,94,95].…”
Section: Minibodies Diabodies Single-chain Variable Region Fragmentmentioning
confidence: 99%
“…The efficient and highly specific binding of PSMA in vivo predetermines 5D3 antibody fragments for further clinical development. This could be directed in parallel to development of other PSMA-specific tools such as bispecific molecules and fusions with toxins and immunological molecules combined alternatively with antimitotic drugs [35,78], conjugates with fluorescent dyes or radioisotopes [16,20,72], and multimeric molecules with potential to activate immune cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, PSMA-specific antibodies are being developed as new PCa-targeting theranostics. Various constructs have already been tested in vitro on PSMA-expressing cells [20] as well as in vivo in relevant xenograft models [16,[21][22][23][24][25]. Notably, PCa imaging in human patients has also been performed using a PSMA-specific 89 Zr-IAB2M minibody [26].…”
Section: Introductionmentioning
confidence: 99%